)Qæ(NSTORÆQ PSIHOLOGÆÇ (B:s)E (NNAW^ALXNIJ POS)QÆBNIK (B/s)E - (NvUKOW(B, (NsERG)QÆJ mIHAJLOWI^(B,s)E; (NvUKOWA(B, (NTETQNA wASIL)QÆWNAs)E ((NkI)QÇW (B:s)E (Ncul(B,s, 2005)
(NzABUT)QÆ TA PROPU]ENÆ STORÆNKI ÆSTORÆÇ PSIHOLOGÆÇs)E
(NoRIG)QÆNAL ZAPISU ZA POSILANNQMs)E
Keywords: (NpSIHOLOG)QÆQs)E -- )Qæ(NSTORÆQ PSIHOLOGÆÇs)E; (NkITAJs; )Qæ(NNDÆQs)E; (NqPON)QÆQs)E; (NsOKOWI^s; (Ng)QÆZELXs)E; (NqWORSXKIJs; (NpROKOPOWI^s; (NkOZA^INSXKIJs; (NkALINOWSXKIJs; (NkONISXKIJs; (NsKOWORODAs; (NkOZELXSXKIJs; (NmAKSIMOWI^s; (N`RKEWI^s; (NwERNADSXKIJs; (Nk)QÆSTQKÆWSXKIJs)E; (NkOST@Ks